The Function of Legal Research in Formulation of Legislation - Victoria Tabita Majesty Lamada; Tetania Retno Gumilang (Jurnal Hukum Prasada, 2020)
The formation of legislation is a condition in the framework of national law development which can only be realized if supported by good methods, which are binding on all institutions authorized to make regulations. Indonesia is a state of law that should implement good national legal development, which is carried out in a planned, integrated and sustainable manner in the national legal system. Law No. 12 of 2011 states that research is an important element in the formation of the legislation process. Because it is impossible if a draft legislation is formed before the existence of a legal investigation. This research discussed about the role of legal research in the formation of legislation, as well as what are the benefits of legal research itself. The conclusion is the formation of laws and regulations cannot occur if there is no legal research, because legal research is an internal problem solver in the process of establishing legislation. This legal research itself plays an active role in obtaining valid, correct, rational, and logical data. In addition, legal research is also useful for obtaining raw materials from all aspects, both juridical, socio-psychological, and philosophical that are accurate and complete.